Stress, Self-Efficacy, Social Support, and Coping Strategies in University Students - Dwyer, Andrea L.; Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
The goal of this study was to examine the relationship of self-efficacy, social support, and coping strategies with stress levels of university students. Seventy-five Education students completed four questionnaires assessing these variables. Significant correlations were found for stress with total number of coping strategies and the use of avoidance-focused coping strategies. As well, there was a significant correlation between social support from friends and emotion-focused coping strategies. Gender differences were found, with women reporting more social support from friends than men. Implications of these results for counselling university students are discussed.